Characterization of Aspergillus nidulans Biofilm Formation and Structure and Their Inhibition by Pea Defensin Psd2 - Corrêa-Almeida, Caroline; Borba-Santos, Luana P.; Rollin-Pinheiro, Rodrigo; Barreto-Bergter, Eliana; Rozental, Sonia; Kurtenbach, Eleonora (Frontiers in Molecular Biosciences, 2022)
In Brazil, approximately four million people contract fungal infections every year, primarily caused by Aspergillus spp. The ability of these fungi to form biofilms in tissues and medical devices complicates treatment and contributes to high rates of morbidity and mortality in immunocompromised patients. Psd2 is a pea defensin of 5.4 kDa that possesses good antifungal activity against planktonic cells of representative pathogenic fungi. Its function depends on interactions with membrane and cell wall lipid components such as glucosylceramide and ergosterol. In the present study, we characterized Aspergillus nidulans biofilm formation and determined the effect of Psd2 on A. nidulans biofilms. After four hours, A. nidulans conidia adhered to polystyrene surfaces and formed a robust extracellular matrix-producing biofilm at 24 h, increasing in thickness until 48 h. Psd2 inhibited A. nidulans biofilm formation in a dose-dependent manner. Most notably, at 10 μM Psd2 inhibited 50 % of biofilm viability and biomass and 40 % of extracellular matrix production. Psd2 significantly decreased the colonized surface area by the biofilm and changed its level of organization, causing a shortening of length and diameter of hyphae and inhibition of conidiophore formation. This activity against A. nidulans biofilm suggests a potential use of Psd2 as a prototype to design new antifungal agents to prevent biofilm formation by A. nidulans and related species.